Languages on Display: Multilingual Signage at Pererenan Beach - Yunanfathur Rahman; Ketut Artawa; Audrey Gabriella Titaley; Ajeng Dianing Kartika; Hasbulloh Nadaraning (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This study describes the language phenomenon that occurs at Pererenan Beach, Badung Regency, Bali. A variety of outdoor signage were found at this beach, such as banners, information boards, signboards, etc. Data was obtained through observation and photographic documentation. The data were then analyzed qualitatively. In these public signs there are interesting language phenomenon, namely the phenomenon we know as multilingualism. Multilingualism that appears in the form of code mixing, bilingualism, and interference. A comparison of data collected from two years shows that outdoor signs at Pererenan Beach need to be made better in the context of aggregate. Aggregate signs at Pererenan Beach are still dominated by non-permanent aggregate signs. A better long-lasting aggregate signs could be made of stone or ceramic components. Although these code mixing, bilingualism, and interference do not lead to misunderstandings in interpreting the information contained in the outdoor signs, but it is still an interesting phenomenon to be discussed.